Parents' Responsibility For Children's Education in Aceh Reviewed From An Islamic Legal Perspective - Muliana, Muliana; Husaini, Husaini; AR, Murniati; Akob, Bachtiar; Aziz, Abdul (Samarah: Jurnal Hukum Keluarga dan Hukum Islam, 2026)
This research aims to explore the responsibilities of parents in their children's education in Aceh from the Islamic legal perspective. How does Islam view the duties of parents in terms of education concerning religion and morality, and what factors influence the fulfillment of these obligations, as well as its application in the unique context of Acehnese social and cultural life, Using qualitative methods with an Islamic legal approach, data was collected through in-depth interviews with parents, religious scholars, and educators, as well as analysis of legal documents and local wisdom. The findings report that Islam has it that one of the major responsibilities for which parents are accountable involves educating the child about religion apart from shaping the child's character. Social facets like the tradition of dayah, meunasah and balee beut, along with community norms support the phenomenon of this responsibility. Yet, modern challenges such as technological influence and changes in upbringing do also have significant effects. In practice, the Acehnese have been able to harmonize Islamic law with local traditions, thus coming up with a unique way that is both religious and adaptive. This research reiterates the importance of the interplay between Islamic law and local tradition in molding character in children and provides a model of religious-based education that is relevant in today's modern age.